A new framework to understand the drivers of policy mixes in multilevel contexts: The case of urban air pollution - Peter Eckersley; Oliver Harrison; Marianna Poberezhskaya (Environmental Policy and Governance, 2022)
The literature on policy mixes tends to focus on the instruments that different jurisdictions adopt to tackle public problems, and how policies may complement or conflict with each other. Fewer studies examine the factors that influence instrument choice, particularly within multilevel contexts, despite a recognition that policy mixes to tackle similar issues vary substantially across and within countries. We present a new framework to help understand and predict policy choice in subnational governance, arguing that the level of local support for action influences the type of policy a city adopts, whereas top-down drivers shape the breadth of instruments it deploys. Drawing on in-depth stakeholder interviews and documentary analysis, we apply this framework to explain why two contrasting English cities selected their own distinctive policy mixes to combat air pollution. We suggest that where top-down drivers for action are strong but bottom-up support is muted, as was the case in Nottingham, municipal governments are likely to adopt a broad range of largely (re)distributive, informational and administrative instruments to tackle policy problems. Where local support is strong, as in Westminster, city authorities prefer to introduce regulations, because restrictions entail fewer political costs in these contexts and are more likely to be effective.
Keywords: 320; air pollution; England; local choice; multilevel governance; policy instruments; policy mixes; transport policy